2015
DOI: 10.1161/strokeaha.114.007568
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Microinfarcts Detected In Vivo on 3 Tesla MRI

Abstract: Background and Purpose— Cortical microinfarcts (CMIs) are a common postmortem finding associated with vascular risk factors, cognitive decline, and dementia. Recently, CMIs identified in vivo on 7 Tesla MRI also proved retraceable on 3 Tesla MRI. Methods— We evaluated CMIs on 3 Tesla MRI in a population-based cohort of 194 nondemented older people (72–80 years) with systolic hypertension. Using a case–control design, participants with and without CMIs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 8 publications
2
66
0
Order By: Relevance
“…trained by S. van Veluw, and uncertain cases were verified by S. van Veluw, who is experienced in rating CMIs on both 7.0T and 3.0T MRI. 3,4,6 The intrarater agreement was good for rating CMIs on 30 randomly selected patients (intraclass correlation coefficient, 0.83). Severity of white matter hyperintensities (WMH) was rated on axial FLAIR using the Age-Related White Matter Changes Scale.…”
Section: Neuropsychological Assessmentmentioning
confidence: 87%
See 2 more Smart Citations
“…trained by S. van Veluw, and uncertain cases were verified by S. van Veluw, who is experienced in rating CMIs on both 7.0T and 3.0T MRI. 3,4,6 The intrarater agreement was good for rating CMIs on 30 randomly selected patients (intraclass correlation coefficient, 0.83). Severity of white matter hyperintensities (WMH) was rated on axial FLAIR using the Age-Related White Matter Changes Scale.…”
Section: Neuropsychological Assessmentmentioning
confidence: 87%
“…1,20,21 To date, CMIs have not been assessed in vivo in stroke populations, which are likely to have a higher vascular risk burden than in patients presenting to memory clinics. Recently, it was shown that cortical CMIs can be visualized with not only 7.0T MRI but also 3.0T MRI, 4,22 making it possible to study the clinical significance and longitudinal consequences of these lesions in living patients. It should be noted that 3.0T MRI has lower sensitivity but similar specificity than 7.0T MRI for the detection of CMIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite lower signal-to-noise ratio and resolution, it seems feasible to recognize chronic gliotic CMIs on 3-tesla MRI as well. 5,[26][27][28] Hemorrhagic CMIs cannot currently be distinguished from primary hemorrhages, both will be regarded as cerebral microbleeds on in vivo MRI. Juxtacortical hyperintense lesions should best be discarded.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization and standardization of assessment protocols for these lesions will support rapid implementation of robust and valid CMI detection in cohort studies throughout the world. This will enable a widespread evaluation of the clinical relevance of CMIs in the context of aging, cerebrovascular disease, and dementia in future clinical studies, both cross-sectional as well as longitudinal 9,10 .…”
Section: Discussionmentioning
confidence: 99%